Spatial gene expression profiling identifies prognostic features of residual tumors after neoadjuvant chemotherapy in triple-negative breast cancer - Won, Hye Sung; Kim, Yong-Seok; Seo, Kyung Jin; Jun, Sun-Young; Sun, Der Sheng; Choi, Mihong; Yoon, Jung-Sook; Byun, Jae Ho (Frontiers in Oncology, 2025)
BackgroundThe standard treatment for early-stage triple-negative breast cancer (TNBC) is neoadjuvant chemotherapy (NAC) followed by surgery, but patients with residual disease have worse outcomes. We investigated genetic alterations related to recurrence using spatial transcriptomic analyses of residual tumors from patients who had and had not relapsed after NAC for early-stage TNBC.MethodsThirteen patients who underwent curative resection after NAC for early-stage TNBC, six of whom experienced recurrence, were included. The residual tumor tissues were stained and analyzed using the NanoString GeoMx Digital Spatial Profiling platform. Changes in gene expression were presented as fold changes compared with the control group, and genes were considered to be differentially expressed if they had an absolute value of log2-fold change ≥ 2.0 at a false discovery rate of < 0.05.ResultsOn comparing gene expression in residual cancer cells, eight genes (S100A9, S100A7, CHI3L1, SLPI, SERPINA3, CASP14, URI1, and AZGP1) were found to be significantly upregulated, and 17 (ACTA2, IGFBP4, BGN, TPM2, MYLK, MMP7, HLA-DPB1, CRISPLD1, COL1A2, OLFM4, KRT14, HLA-DPA1, COL1A1, COL3A1, IFI6, IFI27, and A2M) were significantly downregulated in patients with recurrence. On comparing gene expression in macrophages, six genes (SLPI, PABPC1, AZGP1, SUPT7L, RPL22, and FDCSP) were found to be significantly upregulated, and IFI27 was significantly downregulated in patients with recurrence. No genetic alterations with significant differences were found in T cells. No significant change was observed in the density of macrophages between patients with and without recurrence. However, the density of T cells was relatively lower in patients with than in those without recurrence.ConclusionWe identified some differentially expressed genes relevant to oncogenic signaling and immunosuppressive tumor-associated macrophages. These findings provide novel insights into factors affecting prognosis in patients with residual disease after NAC for early-stage TNBC.